Standardization of Gardenia jasminoides Fruits and Crocin Content Analysis Using UV/visible Spectrophotometry - Onuma Zongram (Science Faculty of Chiang Mai University, 2019)
Crocin is an important source of food colorant that is found in the fruit of Gardenia jasminoides which exhibited various biological activities for the treatment of inflammation, jaundice, headache, edema, fever, hepatitis and hypertension. Standardization of herbal medicines is the process carries out for an assessment of quality, efficacy, safety and reproducibility using various methods. The aim of the current study was to evaluate the microscopic characteristics, physicochemical properties, TLC fingerprint and UV/visible spectrophotometry method for the quantitative estimation of crocin content in the fruit of G. jasminoides. Microscopic inspection of powdered herbal drug showed the presence of plant structural tissue including multicellular trichomes. Physicochemical parameters and TLC fingerprinting were also established. Percentage of total ash value, acid insoluble ash value, loss on drying and moisture content should not more than 4.93, 0.71, 8.85 and 5.02% w/w, respectively while water soluble extractive value and ethanol soluble extractive value should not less than 26.91 and 22.53 % w/w, respectively. UV/visible spectrophotometry method was validated for determination of crocin content. The method validation was performed according to the ICH guideline. The linearity was in the range between 5 and 100 mg/ml (r2=0.999) and exhibited suitable accuracy, precision and robustness. The result of crocin content analysis of G. jasminoides fruits was 7.59 ± 2.64 mg/g of dried crude drug. The established methods in this study can be applied for assessing the standardization and the crocin content in G. jasminoides fruits.